The Strengthening of Responsible Character Through Training Programs at Kaki Dian Emas Foundation Training Institute - Gandi, Parholongan Pamantu (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
This study aims to explore strengthening the character of responsibility through a training program organized by the Kaki Dian Emas Foundation. The focus of the study is to observe how the training program can strengthen the character of responsibility of training participants and explore the efforts made by the training organizing foundation in supporting the program. The design of this study is qualitative with a case study research method. Data collection techniques include interview techniques, direct participation, observation, and documentation. The results of the study indicate that (1) the character training program describes the vision and mission of the Kaki Dian Emas Foundation, Lawang namely making a Training Institution that excels in Spirituality, Education and Character, (2) the implementation of the implementation of the character training program as a strengthening of the character of responsibility at the Kaki Dian Emas Foundation Training institution cannot be separated from the development of religious character values of students. These values are developed through character training that refers to activities and supplies during the specified period, (3) the challenges and supporting factors in strengthening the character of responsibility faced, the diversity of origins of participants and different family backgrounds of participants, how they were raised are challenging factors in improving the character of responsibility of participants. They already have habits and characters that have been patterned since childhood until now. While the supporting factors are in the form of assistance from mentors who accompany, the curriculum system that is applied is the delivery of materials and learning or application in everyday life, all of these factors influence each other and work together in achieving the objectives of this training program plus the Foundation provides supporting facilities in this training program.